Solid waste management strategy as an alternative energy source for economic driver in Kelurahan Gading Kasri,Malang City (International Conference of Graduate School on Sustainability (ICGSS), 2020)
The economic factor is one of the keys to an area that can be said to be advanced and independent, until now the community is still dependent on expensive fuel, while how to use raw materials around the area in the Gading Kasri village is the right idea. One of the ideas to improve the economic factor of the community in the Gading Kasri village is how to convert waste into fuel. The benefits obtained are very large, including helping the community's economy, reducing plastic waste, and turning plastic waste into fuel that is useful for cooking, starting motorbikes, and other fuels. In this research, the design of the Combustion Optimization Tool for the Distillation of Plastic Waste into Oil Fuel (BBM) was made as an effective solution to produce an energy source in the form of gas oil with a maximum volume when compared to previous designs for similar devices. In this design, a plastic waste burner cross-section is made in the form of a circular crossbar so that the volume of waste and the effectiveness of combustion that is collected can be more in volume. Furthermore, this tool will be used by the community in the Gading Kasri Village so that it will be more beneficial for the community or general public.